Research of the possibility of using thermoelectric elements (TEE) in wells with low geothermal gradient - Gabdrahmanova, Klara; Izmailova, Gulnara (Technology audit and production reserves, 2019)
The object of research is wells with a low temperature gradient of less than 2–2.5 °С per 100 m (regions of Tataria, Bashkiria, Udmurtia, etc.). In studying the layout of a device for utilizing geothermal energy, a system analysis method was used. And in the course of the study of the sucker rod pumping unit (SRPU) and the electric centrifugal pumping unit (ECPU), the comparative analysis method is used. The paper discusses the possibility of energy savings in the exploitation of oil fields located in regions with low geothermal potential of development facilities. A method for solving the problem is considered as an option for the integrated use of not only the petrothermal energy of the subsoil, but also the hydrokinetic energy of the formation water. It is shown that the utilization of low-temperature geothermal energy due to its combination with the utilization of the hydrokinetic energy of the water pumped through the RPM system (maintaining reservoir pressure) is economically beneficial. This is due to the fact that the method proposed in the work has a number of features, in particular, production (reactive) wells are equipped at the wellhead with thermoelectric generators that convert the thermal energy of the formation fluid into electrical energy. The use of such devices will reduce the cost of electricity to power the electric drive DPE (deep pumping equipment) and other consumers of electricity in the well. Electricity generated by thermoelectric DC modules is summed from all thermoelectric converters. The received energy is sent along the line to the power supply system of the ACS-TP (automated process control system). Thanks to this, it is possible to obtain electrical energy from low temperature wells. Compared with similar known classical methods, when the gas factor of the produced products is sufficiently high (³80–100 m3/t), the use of associated gas is used to power electric gas and turbine generators that generate power for DPE directly at the production well. However, this method of utilization of associated gas at a late stage of development is not economically feasible, since in this case it is extremely low for its implementation.